Penerapan Pendidikan Karakter Disiplin Di Taman Kanak-Kanak Karya Merdeka Samboja Kutai Kartanegara - Khusni Alhan; Supriyani Supriyani (STAI Publisistik Thawalib Jakarta, 2023)
The aim of the study was to describe the application of disciplinary character education in Karya Merdeka Kindergarten Samboja Kutai Kartanegara. This study used descriptive qualitative research, with the research subjects being teachers and students in class group B2. Data collection techniques with observation, interviews, documentation and questionnaires. The results of the study showed: instilling the character of discipline through activities: (1) a program to habituate smiles, greetings, greetings, being polite and polite to children from an early age. (2) come to school on time by doing line activities together in front of the yard regularly before entering class. (3) get used to lining up neatly when entering class. (4) tidying children's clothes regularly with the aim that children are used to living neatly and cleanly. (5) teach children to store shoes independently on the shoe rack. (6) teach children to tidy up toys that have been used independently. (7) teach children to wash their hands before drinking and eating. (8) teach children to dispose of the canoe in the space provided.